2016
DOI: 10.1186/s41065-016-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation, population structure and linkage disequilibrium in Switchgrass with ISSR, SCoT and EST-SSR markers

Abstract: BackgroundTo evaluate genetic variation, population structure, and the extent of linkage disequilibrium (LD), 134 switchgrass (Panicum virgatum L.) samples were analyzed with 51 markers, including 16 ISSRs, 20 SCoTs, and 15 EST-SSRs.ResultsIn this study, a high level of genetic variation was observed in the switchgrass samples and they had an average Nei’s gene diversity index (H) of 0.311. A total of 793 bands were obtained, of which 708 (89.28 %) were polymorphic. Using a parameter marker index (MI), the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 66 publications
1
15
1
1
Order By: Relevance
“…Almost, similar magnitude of He and I was reported by Said and Kassahun (2015) in Ethiopian population of L. sativum. The LD analysis revealed that the average recombination coefficient (r 2 ) was found to be 0.2010 which was higher than that reported by Zhang et al (2016) in Switchgrass using ISSR markers. Further, the percentage of linkage decay was found to be 16.74% (P \ 0.01).…”
Section: Discussioncontrasting
confidence: 65%
“…Almost, similar magnitude of He and I was reported by Said and Kassahun (2015) in Ethiopian population of L. sativum. The LD analysis revealed that the average recombination coefficient (r 2 ) was found to be 0.2010 which was higher than that reported by Zhang et al (2016) in Switchgrass using ISSR markers. Further, the percentage of linkage decay was found to be 16.74% (P \ 0.01).…”
Section: Discussioncontrasting
confidence: 65%
“…These values are very close to the earlier reports by Amirmoradi et al [ 44 ] wsho reported 85.7–100% and 86.6–100% in ISSR and SCoT, respectively. Zhang et al [ 54 ] reported similar values (ISSR: 82.35–96%; SCoT: 81.25–100%) in a different plant species called Switch grass. Many other reports with other marker systems showed lower percent polymorphisms relative to our findings in this study.…”
Section: Discussionmentioning
confidence: 82%
“…The SCoT marker was utilized for its simplicity, its ability to target gene sequences, and for being a dominant marker . Moreover, ISSR is another common marker for evaluating genetic diversity and is characterized by high polymorphism and recurrence . The objectives of this study are to identify different isolates of Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%